Hand Washing Equipment with Liquid Soap: Innovation for Proper Hand Washing - พุฒิกานนท์ กิตติ; แสงแก้ว คำพล; ดอนหัวรอ สมนึก (Disease Control Journal, 2018)
World Health Organization indicated that diarrhea was the important cause of illness and death in children because they neglected how to wash hands properly. Despite some soap was placed near the faucet but the children rarely used it to wash their hands. This situation led to the concept of making the new equipment which could pump few liquid soap out before the water flow when the students opened the faucet. This innovative research was conducted with an objective of inventing the hand washing equipment in order to help cleaning hand in every washing. Twelve schools were selected purposively in 2 provinces of public health region 17 ( 3 districts of each provinces). Methodology used was hand washing behavioral survey, followed by equipped the innovative hand washing sets and trained the students how to use them correctly Satisfactory survey was done afterward. The results of behavioral survey showed the student always washed their hands before meal and after toilet at 53.3 % and 64.1 % respectively. However, it was obvious that the students who cleaned their hands with soap were just only 46.4%. After 143 hand washing equipments with liquid soap had been set and the students had been trained, 495 students were selected randomly for question naires in 3 months later. It was found that 87.4% of students was satisfied for these equipments and 88.5% of them gave their opinions that this innovation was beneficial equipment. In drawbacks, some students thought they was more waste of water and soap ( 17.2% and 22.1% consequently) but most of them (86.6%) still wanted to use the equipments. This equipment was registered by the Department of Intellectual Property. However, hand washing behavior with this innovative equipment should be studied further to explore whether it could affect the change in hand washing behavior in children in long term basis manner.